Membangun Koperasi Lewat Berjejaring - Muhammad Arsad Dalimunte (Jurnal Maksipreneur, 2012)
Cooperatives are economic organizations whose base is cooperation. The similarity of perceptions, beliefs, and the spirit of collectivity is the capital of cooperatives. In a cooperative organization, prosperity is the impact of cooperation. In a broader scope, to be developed cooperative must network with other cooperatives.